Innovative business groups: territory-based industrial policy in Spain - Josep-Antoni Ybarra-Pérez; Rafael Doménech-Sánchez (European Regional Science Association (ERSA), 2011)
On the last decades, European countries have increased their focus on local production systems as a matter of industrial policy measures. Based on the works related to industrial districts of Becatini (1989), Brusco (1990), Ybarra (1991 and 1996) and Dei Ottati (1994), or the later contributions of Porter (1998a) about productive clusters, Governments have taken measures to stimulate the creation and strengthening of clusters. However, the progressive extension of cluster policies has highlighted the constraints of rationality on which it is based and the criteria used to evaluate their impact and effectiveness. Consequently, the traditional arguments based on the neoclassical concept of efficiency and the advantages of external economies have given way to a new paradigm that gives a central role to organizational learning, collective decision-making and networks as governance structure. The new approach to the analysis of production networks exceeds the territorial or sectorial boundaries to highlight the dynamic and complex nature of the relationships established between actors in the cluster. The approach of governance, as a starting point for the analysis of production networks, opens a new perspective in the assessment of the potential impact of cluster development and the effectiveness of measures aimed to their promotion. Based on the theoretical premises above mentioned, this paper aims to the analysis and valuation of the aid scheme of Innovative Business Partnerships (AEI) sponsored by the Spanish government. This study is based both on traditional analysis of the implementation and impact indicators, as in the analysis of the AEI program's ability to promote the adoption of models of governance and collective action to enhance the competitive capabilities of the cluster.
Keywords: 330